Vaccines, Medicines and COVID-19 How Can WHO Be Given a Stronger Voice? - Velásquez, Germán (SpringerBriefs in Public Health,, 2022)
This open access book is a collection of research papers on COVID-19 by Germán Velásquez from 2020 and early 2021 that help to answer the question: How can an agency like the World Health Organization (WHO) be given a stronger voice to exercise authority and leadership? The considerable health, economic and social challenges that the world faced at the beginning of 2020 with COVID-19 continued and worsened in many parts of the world in the second-half of 2020 and into 2021. Many of these countries and nations wanted to explore COVID-19 on their own, sometimes without listening to the main international health bodies such as WHO, an agency of the United Nations system with long-standing experience and vast knowledge at the global level and of which all countries in the world are members. In this single volume, the chapters present the progress of thinking and debate - particularly in relation to drugs and vaccines - thatwould enable a response to the COVID-19 pandemic or to subsequent crises that may arise. Among the topics covered: COVID-19 Vaccines: Between Ethics, Health and Economics Medicines and Intellectual Property: 10 Years of the WHO Global Strategy Re-thinking Global and Local Manufacturing of Medical Products After COVID-19 Rethinking R&D for Pharmaceutical Products After the Novel Coronavirus COVID-19 Shock Intellectual Property and Access to Medicines and Vaccines The World Health Organization Reforms in the Time of COVID-19 Vaccines, Medicines and COVID-19: How Can WHO Be Given a Stronger Voice? is essential reading for negotiators from the 194 member countries of the World Health Organization (WHO); World Trade Organization (WTO) and World Intellectual Property Organization (WIPO) staff participating in these negotiations; academics and students of public health, medicine, health sciences, law, sociology and political science; and intergovernmental organizations and non-governmental organizations that follow the issue of access to treatments and vaccines for COVID-19.